THE IMPACT OF ACCOUNTING DISCLOSURE IN THE FINANCIAL STATEMENTS ON THE MARKET VALUE SHARE OF COMMERCIAL BANKS LISTED IN THE IRAQ STOCK EXCHANGE - Abdulhussein Hiloalkiabi, Jaafar (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2023)
The research aims to indicate the effect of the relationship between the accounting disclosure related to the suitability of the accounting information provided by the financial statements of the external user in the market value of the share by applying it to the companies listed in the Iraq Stock Exchange. Several statistical measures such as measures of central tendency represented by the arithmetic mean, standard deviation and simple linear regression. To test the research hypothesis, the statistical package for social sciences (spss) program was applied to analyze the questionnaire. The research reached a number of results, the most important of which is that there is a statistically significant relationship between the level of disclosure in the financial reports And the market value of the share at the date of publication of these reports, and the most important recommendations were the need for banks to expand the disclosure of the information contained in the financial statements, which works to increase the confidence of users in them, and reflects positively on the prices of shares in the market along with the level of profitability of banks and their distributions.